Pengaruh Debit Aliran Terhadap Debit Sedimen Di Saluran Sekunder 1 Daerah Irigasi Sidarahayu Kecamtan Purwadadi Kota Banjar - Heri Ali Rifa'i; Iskahar; Salim, Agus (Casuarina: Jurnal Teknik Lingkungan, 2024)
Sediment is a deposit or also known as grains of soil which are usually dissolved in water or which settle at the bottom of channels caused by erosion on the surface of the land, ravines, ditch erosion and erosion on cliffs. This research focuses on finding the relationship between flow discharge and sediment discharge and finding the maximum capacity of irrigation channels. The aim of this research is to determine the relationship between flow discharge and elevated sediment discharge in secondary irrigation 1 Sidarahayu Irrigation Area, Purwodadi District, Banjar City and to determine the maximum channel capacity discharge that the channel can accommodate after and before the presence of sediment. By using the Simple Regression Equation Analysis Method and mathematical Capacity calculations. From this research, the results of a simple linear regression equation are Qs = 0.269+ 0.013677 Q with a value of = 0.89. The maximum capacity of the channel that can be accommodated before the presence of sediment is 30,569 /s and after the presence of sediment is 25,323 /s.